Can news sites stimulate online deliberation? A study of readers comments posted on Folha.com - Sampaio, Rafael Cardoso; Barros, Samuel Anderson Rocha (Brazilian journalism research, 2012)
This paper assesses online deliberation on readers’ comments on the website of the Brazilian newspaper Folha de S. Paulo. To this end, 260 posts on four different stories were analyzed. In addition to the comments, the newspaper’s website, its discursive tools and the political stance of the participants, were examined. It was concluded that there was relevant deliberativeness in discussions but also excessive aggressiveness among participants. The comments posted revealed that most of the participants sought to win debates rather than promoting mutual understanding. Lastly, the paper discusses how to deal normatively with this aggressiveness and attempts to identify ways to increase democratic values through the provision of discursive tools by news sites.